Anesthesia and Analgesia Practice Pathway Options for Total Knee Arthroplasty: An Evidence-Based Review by the American and European Societies of Regional Anesthesia and Pain Medicine. Issue 6 (November 2017) - Kopp, Sandra L.; Børglum, Jens; Buvanendran, Asokumar; Horlocker, Terese T.; Ilfeld, Brian M.; Memtsoudis, Stavros G.; Neal, Joseph M.; Rawal, Narinder; Wegener, Jessica T.
Abstract : Abstract: In 2014, the American Society of Regional Anesthesia and Pain Medicine in collaboration with the European Society of Regional Anaesthesia and Pain Therapy convened a group of experts to compare pathways for anesthetic and analgesic management for patients undergoing total knee arthroplasty in North America and Europe and to develop a practice pathway. This review is intended to be an analysis of the current literature to assist individuals and institutions in designing a pathway for total knee arthroplasty that is based on existing evidence and expert recommendation and may be customized according to individual settings.